APPLICATION OF CONJUGAL VISIT IN THE INDONESIAN STATUTORY SYSTEM FOR CORRECTIONAL ASSISTED PERSONS - Heliany, Ina; Sihotang, Muhenri (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2022)
The problem of meeting the sexual needs or biological needs of prisoners is a problem that is often the cause of chaos in prisons. The non-channeling of these needs sometimes causes the inmate's emotions to become uncontrollable. In Indonesia, some provisions allow married prisoners to gather with their families through CMK (Family Visiting Leave) as stipulated in the Decree of the Minister of Justice of the Republic of Indonesia Number: M.01-PK.03.02 of 2001 concerning Family Visiting Leave for Prisoners. This regulation provides an opportunity for married inmates to go to their family's residence for 2 (two) days or 2 x 24 hours to allow the married prisoner to meet his sexual needs while taking time off. However, in practice, these regulations have yet to be maximized because this is often used by officers and has become a topic of discussion in the mass media. Various opinions and studies mention the need for prisoners to be given this right, one of which is the Conjugal Visit policy. Conjugal Visit is also often referred to as the "Romance Chamber". Based on this, researchers are interested in researching how the Indonesian Law Regulation system regulates conjugal visits. The method used is the Normative Juridical method. They are namely answering problems through literature both primary, secondary and tertiary. The assumption found is that Cobjugal Visit has yet to be regulated and has no legal umbrella. However, this is a basic right for every human being having his status, whether he is a Prisoner or a free man.